On a Good Literature - Jakubowski, Piotr (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
The thesis discussed here is that a main subject of literature is evil while its main goal is good. Is it possible that depicting the evil (crime,suffering, cruelty) could causes in good consequences (for reader or author)? Three main justifications of depicting of the evil in literfor it or help toature claim that it could sensitize reader for it, immune for it or help to. But all of those justifications – as it is shown by lecture of J.M. Coetzee’s Elizabeth Costello and J. Marías Your Face Tomorrow – are at least problematic. It is impossible to determine a priori whether a reader become “a better person” after contact with the evil inscribed in literary works, or, on the contrary, will be anesthetized or even possessed by the evil. So, as a solution, author recalls a concept of a “good story”, which paradigm is a speech on deathbed, enclosing whole life of a moribund and – with the burden of finality and frankness – asking not whether you was acting good or bad, but whether the fictions you were living by them were worth it. A “good literature” shows its figures as entangled infictions – frames of reference which provide a meaning to the world and are responsiblefor a essential distinctions, headed with this for good and bad things and behaviors. Alldepends for the fictions we entrust and affirm – it says – and our moral duty, as well as writer’s responsibility, is to be vigilant for its real consequences – the places where fiction meets real body of other human being capable for suffering.